Strategies for Disrupting Illegal Firearm Markets : a Case Study of Los Angeles. - Ridgeway, Greg (RAND Corp., 2008)
Could a data-driven, problem-solving approach yield new interventions to disrupt local, illegal gun markets serving criminals, gang members, and juveniles in Los Angeles? Law enforcement can analyze patterns in crime-gun data to trace illicit firearm acqu.